Challenges and added value of measuring embodied variables in psychotherapy - Nyman-Salonen, Petra; Kykyri, Virpi-Liisa; Penttonen, Markku (Frontiers in Psychiatry, 2022)
Research on embodied aspects of clinical encounters is growing, but discussion on the premises of including embodied variables in empirical research is scarce. Studies have repeatedly demonstrated that embodied aspects of psychotherapy interaction are vital in developing a therapeutic alliance, and these should be considered to better understand the change process in psychotherapy. However, the field is still debating which methods should be used and which features of the embodied aspects are relevant in the clinical context. The field lacks methodological consistency as well as a theoretical model. In the Relational Mind research project, we have studied the embodied aspects of interaction in the context of couple therapy for almost a decade and have gained experience with the positive and negative aspects of studying embodied variables in quantitative and qualitative studies. We have set out to develop the methodology (or procedures) for studying embodied variables in a multiperson setting, concentrating on interpersonal synchrony of sympathetic nervous system responses and movements, and we have strived to create methods for integrating information from different embodied modalities. In this narrative review, we share our experiences of the challenges and added value of studying embodied aspects in psychotherapy. The research field urgently needs an ongoing discussion of what researchers should take into consideration when studying the embodied aspects of interaction. We urge researchers to collaborate between research groups to jointly decide on the basic parameters of studies on the different embodied modalities of the research so that the individual researcher can become more aware of the impact the methodological choices have on their studies, results, and interpretations. We also see the use of embodied variables as having added value in the clinical work of psychotherapists, since it not only deepens our understanding about what is helpful in psychotherapy but will enable fine-tuning therapy processes to better suit clients who are verbally less fluent.